Experimental Evaluation of Multi-Path Routing in a Wireless Mesh Network Inside a Building - Staub, Thomas; Ott, Stefan; Braun, Torsten (Electronic Communications of the EASST, 2009)
Multi-path routing can provide robustness and load balancing to com- munication in wireless mesh networks (WMNs). We present a Linux implementation of an existing multi-path routing scheme and evaluate it in our inhouse WMN testbed. In addition to our implementation, we describe the testbed where we performed evaluations regarding end-to-end delay and packet loss. Furthermore, we identify the limitations of the implemented protocol in a real-world scenario with interferences due to dense node placement as well as third-party networks and discuss possible enhancements and general directions of research.